An evaluation of the effects of a service change from epidurals to rectus sheath catheters on postoperative pain. (July 2013) - Finch, L.; Phillips, A.; Acheson, N.; Dix, P.; Berry, C.
<x xml:space="preserve">Abstract</x> Epidurals are frequently used as part of multi-modal perioperative analgesia. They are widely accepted as providing excellent pain relief but are associated with side-effects, have a significant failure rate and can limit a patient's mobility. We report on our use of rectus sheath catheters (RSCs), in conjunction with intravenous opiate via patient controlled analgesia (PCA), as a means of providing analgesia post-laparotomy for gynaecological oncological patients. Our experience is that this offers an alternative method of providing equivalent analgesia, avoiding the risks associated with epidural use and possibly has a role in reducing length of patient stay, although this requires further investigation.